2023
DOI: 10.1002/eap.2819
|View full text |Cite|
|
Sign up to set email alerts
|

Biotic resistance to fish invasions in southern China: Evidence from biomass, habitat, and fertility limitation

Abstract: Understanding the mechanisms underlying the invasion success or failure of alien species can help to predict future invasions and cope with the invaders. The biotic resistance hypothesis posits that diverse communities are more resistant to invasion. While many studies have examined this hypothesis, the majority of them have focused on the relationship between alien and native species richness in plant communities, and results have often been inconsistent. In southern China, many rivers have been invaded by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Cannibalism may be associated with the additive and synergistic impacts of habitat degradation and biological invasions for various reasons. Firstly, because natural and diversified ecosystems tend to sustain more complex trophic interactions and greater resistance to invasions (i.e., Biotic Resistance Theory; Elton, 1958; Gu et al., 2023). This can translate into greater availability of native prey (lower cannibalistic propension) in the diet and a lower abundance of predators.…”
Section: Discussionmentioning
confidence: 99%
“…Cannibalism may be associated with the additive and synergistic impacts of habitat degradation and biological invasions for various reasons. Firstly, because natural and diversified ecosystems tend to sustain more complex trophic interactions and greater resistance to invasions (i.e., Biotic Resistance Theory; Elton, 1958; Gu et al., 2023). This can translate into greater availability of native prey (lower cannibalistic propension) in the diet and a lower abundance of predators.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding why some communities are more readily invaded than others is a primary goal of invasion ecology and conservation biology. The study by Gu et al (2023) supported the biotic resistance hypothesis in freshwater ecosystems and suggested that protecting freshwater fish diversity is an important and effective pathway to mitigate the impacts of alien fishes.…”
Section: Mechanisms Of Invasion Successmentioning
confidence: 90%